Mortality risk factors during readmission at the Department of Medicine - Trakulthong C; Phunmanee A (Dove Medical Press, 2017)
Chayanis Trakulthong, Anakapong Phunmanee Department of Medicine, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand Background: Readmission is an indicator of quality of inpatient care. A study from Hong Kong found readmission mortality rate to be 5.1%. There are limited reports on risk factors for mortality other than co-morbid diseases in readmission patients. This study, thus, aims to evaluate risk factors for mortality during readmission.Methods: This study was conducted at a university hospital in Thailand. The inclusion criteria were patients aged ≥15 years and readmission to internal medicine wards within 28 days after discharge. The outcome of the study was death during readmission. Risk factors for readmission mortality were analyzed using multivariate logistic regression analysis.Results: There were 10,389 admissions to the Department of Medicine, Khon Kaen University, of which 407 required readmission (3.90%). Of those patients, 75 (18.43%) died during readmission. There were 6 independent factors associated with death in patients who were readmitted, including advanced age (>60 years), presence of more than 2 co-morbid diseases, admission duration of >14 days, fever at previous discharge, low hemoglobin (<12 g/dL), and having undergone over 5 procedures.Conclusion: Older age, co-morbid diseases, readmission duration, presence of low hemoglobin at previous discharge, and numbers of procedures at readmission were significantly associated with increased mortality risk for readmission patients. Keywords: readmission, mortality, predictors